A hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor and preparation method thereof

By developing hydrogel nanomaterials loaded with photosensitizers and epidermal growth factors, using photodynamic therapy and targeted bactericidal effects, the shortcomings of existing hydrogel dressings in treating bacterial infection wounds are solved, and the effect of efficient bactericidal, promoting healing and reducing drug resistance is achieved.

CN119215221BActive Publication Date: 2025-04-01HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411340751.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-01
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing hydrogel dressings have problems such as limited application range when dealing with bacterial infection wounds, difficulty in fully covering and filling the entire wound area, frequent replacement, and unrestrained fixation. Traditional antibiotic therapy can easily lead to bacterial resistance.

Method used

A hydrogel nanomaterial loaded with photosensitizers and epidermal growth factors was developed to synthesize positively charged hydrogel nanoparticles, and load the photosensitizer TPA-2PY-C2 and epidermal growth factor EGF on it to form AIE-EGF-NPs nanoparticles, and use photodynamic therapy and targeted bactericidal effects to improve the antibacterial effect.

Benefits of technology

It achieves efficient bactericidal of bacteria, reduces the production of bacterial resistance, has good cytocompatibility and hemocompatibility, can promote wound healing, and has multiple effects, including antibacterial, anti-inflammatory and promoting healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215221B_ABST
    Figure CN119215221B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of functional polymer materials, and specifically relates to a hydrogel nanomaterial loaded with a photosensitizer and an epidermal growth factor and a preparation method thereof. The preparation method includes preparing hydrogel nanoparticles NPs, loading a photosensitizer, and preparing AIE-EGF-NPs nanoparticles. The product of the present invention has better uniformity and dispersibility than simple antibacterial materials, and has better antibacterial effect than traditional wound dressings. The product of the present invention has good biocompatibility. In a full-thickness wound model of mice infected with Staphylococcus aureus, the hydrogel nanoparticles show obvious functions of promoting wound healing and preventing wound infection. In addition, histological analysis of mouse organs by H&E staining showed that the hydrogel nanoparticles are a safe therapy for treating wound healing. Therefore, the hydrogel nanoparticles can greatly promote the healing process of the wound and have potential application value in the biomedical field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional polymer materials, and in particular relates to a hydrogel nanomaterial loaded with a photosensitizer and an epidermal growth factor and a preparation method thereof. Background Art

[0002] The skin is the body's primary defense organ, playing a vital role in protecting against external damage and avoiding internal water loss. However, once the integrity of the skin is compromised, pathogens can penetrate the body, leading to a variety of consequences, including pain, bleeding, infection, inflammation, prolonged healing time, and scar formation. In addition, pathogen invasion may lead to severe infection and inflammation, which will inevitably lead to chronic wound healing, causing long-term suffering to patients.

[0003] To date, antibiotics are still the most effective means of treating bacterial infections, but the overuse of antibiotics has led to bacterial resistance, followed by the emergence of multidrug-resistant strains, which is a huge challenge to the efficacy of traditional antibiotics. Therefore, it is of great significance to develop new antibacterial agents with high antibacterial activity and not easy to cause bacterial resistance. The use of metal ions for sterilization and disinfection has a very long history. The reason why metal ions can have a certain bactericidal effect is that after the positively charged metal ions combine with the negatively charged bacterial surface, the metal ions can further penetrate the cell wall and cause it to rupture, causing the loss of bacterial cell components and ultimately leading to bacterial death. In addition, metal ions also interfere with bacterial metabolism and enzyme activity, which will affect the normal physiological function of bacteria. Common metal ions such as silver ions, copper ions, zinc ions and lead ions have been reported as bactericidal and disinfectant applications. However, the toxicity of metal ions to normal body cells cannot be ignored, so when designing such nanomaterials, their biosafety issues cannot be ignored. Ideal wound dressings need to provide a moist environment, good self-repair ability and antibacterial ability. Hydrogel dressings are one of the most widely used dressings in clinical practice due to their high hydrophilicity and excellent biocompatibility. However, hydrogel dressings also have some disadvantages when treating bacterially infected wounds. First, their scope of application is limited, and they are not suitable for deep or tunnel-shaped wounds, and it is difficult to completely cover and fill the entire wound area. In addition, for wounds with more exudate, hydrogels need to be replaced frequently, which increases the workload and cost of care. Furthermore, due to the soft texture of hydrogels, they may not be firmly fixed on the wound, so additional fixing measures are needed to keep the dressing stable.

[0004] Antimicrobial photodynamic therapy is a non-invasive, clinically approved and safe treatment strategy. It can effectively kill bacterial pathogens and is not prone to drug resistance. In photodynamic therapy, photosensitizers can absorb visible light and be excited to a high-energy singlet state. However, the spin of excited electrons is unstable, resulting in a short lifetime. The excited state molecules can be converted to a longer-lived triplet state through redox reactions or intersystem crossing. In photochemical reactions, they are mainly carried out through type I and type II mechanisms. In type I reactions, triplet molecules transfer electrons to substrates, thereby generating superoxide anions and hydroxyl radicals. These reactive oxygen species can cause irreversible oxidative damage to bacterial cell membranes and other biomolecules. In type II reactions, excited triplet molecules react with molecular oxygen to generate highly reactive singlet oxygen through an energy transfer process. The generated singlet oxygen can effectively eliminate bacterial pathogens. Photosensitizer, light source and molecular oxygen are the three basic prerequisites for photodynamic therapy. However, most literature reports that photosensitizers have poor hydrophilicity and poor bioavailability, which minimizes cell membrane adhesion and penetration. In addition, due to the short half-life of singlet oxygen and free radicals in the biological microenvironment, the target localization of photosensitizers is crucial to achieve efficient photodynamic effects. Therefore, different strategies are developed to improve the solubility / dispersibility and photodynamic efficacy of photosensitizers against various pathogens. Therefore, it is urgent to develop polymer matrix materials that are non-toxic, can simulate functional organs to reduce inflammatory responses, have photon receiving capabilities, and can transfer excitation energy to photosensitizers for enhanced photodynamic therapy applications. Summary of the invention

[0005] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a hydrogel nanomaterial loaded with a photosensitizer and an epidermal growth factor and a preparation method thereof.

[0006] The purpose of the present invention is achieved by the following technical solution: a method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor, which comprises the following steps:

[0007] S1. Preparation of hydrogel nanoparticles NPs:

[0008] A mixed aqueous solution of N-isopropylacrylamide, methacrylamidopropyltrimethylammonium chloride and N,N-methylenebisacrylamide, and an anhydrous ethanol solution of N-tert-butylacrylamide are added to a reaction bottle, and then a surfactant and an initiator are added, and the reaction is carried out under a nitrogen atmosphere. The reaction temperature is 50-65° C., the reaction time is 4-8 hours, and the reaction mixture is post-treated to obtain hydrogel nanoparticles NPs;

[0009] S2. Loading photosensitizer:

[0010] The photosensitizer TPA-2PY-C2 is loaded on the hydrogel nanoparticles NPs prepared in step S1, and AIE-NPs are obtained after purification and freeze-drying;

[0011] S3. Preparation of AIE-EGF-NPs nanoparticles:

[0012] The AIE-NPs prepared in step S2 are mixed with the epidermal growth factor (EGF) solution and incubated for 10 to 14 hours. AIE-EGF-NPs nanoparticles are obtained after purification and freeze-drying.

[0013] Furthermore, in the mixed aqueous solution in step S1, the concentration of N-isopropylacrylamide is 3-4.5 mg / mL, the concentration of methacrylamidopropyltrimethylammonium chloride is 0.35-0.45 mg / mL, and the concentration of N,N-methylenebisacrylamide is 0.2-0.3 mg / mL.

[0014] Furthermore, the concentration of N-tert-butylacrylamide in the anhydrous ethanol solution of N-tert-butylacrylamide in step S1 is 108-124 mg / mL.

[0015] Furthermore, in step S1, the surfactant is sodium dodecyl sulfate, and the initiator is ammonium persulfate.

[0016] Furthermore, the volume ratio of the mixed aqueous solution to the anhydrous ethanol solution of N-tert-butylacrylamide is 45-55:1, the volume ratio of the total mass of the surfactant and the initiator to the mixed aqueous solution is 1 mg:1.5-2 mL, and the mass ratio of the surfactant and the initiator is 37.5-100:1.

[0017] Furthermore, the post-treatment in step S1 is to dialyze and purify the reaction mixture in ultrapure water for 110 to 130 hours using a dialysis bag with MWCO1400, and the dialysate is freeze-dried to obtain a white flocculent as hydrogel nanoparticles NPs.

[0018] Furthermore, during the heating process, the compounds 1-ethyl-4-methylpyridinium iodide and tetrahydropyrrole are added to the ethanol solution of 4,4,-diformyl triphenylamine with a concentration of 48-56 mg / mL, the mass volume ratio of the compound 1-ethyl-4-methylpyridinium iodide to the ethanol solution of 4,4,-diformyl triphenylamine is 65-75 mg / mL, and the volume ratio of tetrahydropyrrole to the ethanol solution of 4,4,-diformyl triphenylamine is 2-3:1, and the resulting mixture is stirred at 75-85°C for 15-17 hours, and the resulting product is TPA-2PY-C2.

[0019] Furthermore, a TPA-2PY-C2 solution with a concentration of 800 to 1200 μM is mixed with the hydrogel nanoparticles NPs prepared in step S1 and stirred and incubated for 10 to 14 hours. After the incubation, the mixture is dialyzed and purified in ultrapure water using a dialysis bag with MWCO1400 for 68 to 75 hours. The dialysate is freeze-dried to obtain an orange flocculent, which is AIE-NPs. The mass volume ratio of the hydrogel nanoparticles NPs to the TPA-2PY-C2 solution is 1 to 2 mg: 5 mL.

[0020] Furthermore, the protein concentration of the epidermal growth factor EGF solution in step S3 is 8-12 μg / mL, the mass volume ratio of AIE-NPs to epidermal growth factor EGF solution is 30-40 mg:1 mL, and after the incubation, the mixture is dialyzed and purified in ultrapure water with a MWCO1400 dialysis bag for 22-26 hours, and the dialysate is freeze-dried to obtain the flocs, which are AIE-EGF-NPs.

[0021] The hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor is prepared by the above method.

[0022] In the present invention, relatively hydrophobic monomers N-tert-butylacrylamide (TBAm) and temperature-responsive monomers N-isopropylacrylamide (NIPAm) are used as the main components, a small amount of cationic monomers methacrylamidopropyltrimethylammonium chloride (MAPTAC), crosslinking agent N,N-methylenebisacrylamide (Bis), sodium dodecyl sulfate (SDS) as an emulsifier, ammonium persulfate (APS) as an initiator, and the reaction is carried out under a nitrogen atmosphere to synthesize hydrogel nanoparticles NPs. Among them, TBAm is used as a hydrophobic unit to provide a hydrophobic region, and NIPAm polymer is a common temperature-responsive material. When the reaction temperature is higher than the lowest critical solution temperature (LCST) of NIPAm polymer, NIPAm polymer undergoes a rolling ball effect, that is, the polymer chain shrinks to form nanoparticles; the cationic monomers MAPTAC provide positive charges, which enhance the ionic conductivity of the polymer and the interaction with negatively charged Gram bacteria on the cell surface; Bis is used as a crosslinking agent to increase the strength and stability of the polymer.

[0023] The monomers of the whole system open double bonds through addition polymerization to form new free radicals, which continue to react with other monomers to gradually form long-chain polymers, and the temperature is raised to produce a rolling ball effect to obtain spherical polymers. TBAm has hydrophilicity, which can increase the water solubility of the polymer, and the introduction of hydrophobic side chains can prepare polymers with good water retention and mechanical strength. At the same time, the introduction of three single bonds can increase the flexibility and processability of the polymer to provide conditions for the subsequent loading of photosensitizers and epidermal growth factor (EGF); in order to make the final product injectable and targeted, the present invention synthesizes a polymer in the form of nanospheres.

[0024] The synthesis route of the hydrogel nanoparticles NPs of the present invention is:

[0025]

[0026] The present invention has the following advantages:

[0027] (1) The product of the present invention proposes a new preparation formula for hydrogel nanoparticles by changing the hydrogel monomers. The hydrogel monomers with positively charged groups are introduced into the hydrogel system, so that the hydrogel nanoparticles are targeted to the negatively charged Gram-like bacteria on the cell surface through electrostatic action and tightly adsorbed to achieve a targeted bactericidal effect.

[0028] (2) The antibacterial activity of the hydrogel nanoparticles AIE-EGF-NPs of the present invention comes from the fact that the photosensitizer receives light of a specific wavelength, absorbs photons, causes the photosensitizer molecules to transition from the ground state to the excited state, and generates reactive oxygen species (ROS) that cause oxidative damage to surrounding biological molecules, thereby achieving a bactericidal effect. This method has the advantages of being non-invasive, broad-spectrum antibacterial, and not producing drug resistance. At the same time, photodynamic therapy can achieve precise positioning, and treatment can be performed in a specific area through selective illumination, reducing damage to surrounding tissues.

[0029] (3) The hydrogel nanoparticles AIE-EGF-NPs of the present invention have good cell compatibility and blood compatibility, can effectively reduce foreign body reactions in the body, and will not cause obvious inflammation or immune response.

[0030] (4) The hydrogel nanoparticles AIE-EGF-NPs of the present invention can not only achieve a highly effective bactericidal effect, but also achieve an anti-inflammatory function to promote wound healing due to the introduction of epidermal growth factor (EGF).

[0031] (5) The nanometer-scale particle size gives the antibacterial hydrogel nanoparticles a variety of usage forms. They can be administered in a simple spray form, which not only solves the problem of difficult dressing changes faced by ordinary excipients, but is also not restricted by the shape of the wound. They can also be used for minimally invasive delivery of hydrogels. The advantage is that the size of the hydrogel particles is smaller than the inner diameter of most needles. The small size not only allows them to be injected in a needle shape, but also facilitates large-area contact with biological tissues, while facilitating natural metabolic clearance and having stronger tissue penetration ability. The cross-linked network structure of the hydrogel itself can prevent the invasion of various proteins, preventing drug molecules from being degraded by enzymes that invade the hydrogel, thereby maintaining biological activity.

[0032] (6) The product of the present invention has multiple functions. Compared with simple antibacterial materials, the product of the present invention has better uniformity and dispersibility. Compared with traditional wound dressings, this product has better antibacterial effect and can promote wound healing and prevent wound infection. The present invention has good biocompatibility. In the full-thickness wound model of mice infected with Staphylococcus aureus, the hydrogel nanoparticles showed obvious function of promoting wound healing. In addition, histological analysis of mouse organs (liver, spleen, kidney, heart and lungs) was performed by H&E staining to study the in vivo toxicology of hydrogel nanoparticles. After 14 days of treatment in mice, no abnormal effects and obvious organ damage were observed, indicating that the hydrogel nanoparticles are a safe therapy for treating wound healing. These results show that the hydrogel nanoparticles can greatly promote the healing process of wounds and have potential application value in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The particle size distribution of hydrogel nanoparticles NP1-NP4 measured by dynamic light scattering (DLS) and the SEM images of hydrogel nanoparticles NP1-NP4.

[0034] Figure 2 Characterization diagram of hydrogel nanoparticles, where a is the ultraviolet absorption of hydrogel nanoparticles with different particle sizes after drug loading; b is the generation of reactive oxygen; c is the generation of singlet oxygen; d is the change in nanoparticle size within five days; e is the drug release rate of nanoparticles within five days; f is the potential analysis.

[0035] Figure 3 Characterization diagram of the antibacterial properties of hydrogel nanoparticles AIE-EGF-NPs, where a is the flat coating of nanoparticles with different mass concentrations; b is the growth curve of nanoparticles co-incubated with Staphylococcus aureus; c is the growth curve of nanoparticles co-incubated with Escherichia coli.

[0036] Figure 4 SEM images of Gram bacteria and Gram bacteria treated with nanoparticles AIE-EGF-NPs.

[0037] Figure 5 These are the experimental results of the biocompatibility of hydrogel nanoparticles AIE-EGF-NPs, including: a L929 cell laser confocal image; b cck-8 toxicity results at different mass concentrations; c cck8 toxicity results of each component; d hemolysis experiment.

[0038] Figure 6 This is a graph showing the results of a cell migration experiment.

[0039] Figure 7The figures are the results of the mouse wound healing experiment, where a is the photos of skin wounds in different treatment groups from day 0 to day 9, b is the skin wound healing rate in different treatment groups, c is the weight change of mice in different treatment groups, and d is the H&E and Masson staining of wound tissue in the control group and AIE-EGF-NPs+L group on the 14th day.

[0040] Figure 8 This is the result of H&E staining experiment on the main organs of mice. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with the accompanying drawings and examples. The protection scope of the present invention is not limited to the following: Example 1: A method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor, which comprises the following steps: S1. Preparation of hydrogel nanoparticles NPs:

[0042] A mixed aqueous solution of N-isopropylacrylamide, methacrylamidepropyltrimethylammonium chloride and N,N-methylenebisacrylamide, and an anhydrous ethanol solution of N-tert-butylacrylamide are added to a reaction bottle, the volume ratio of the mixed aqueous solution to the anhydrous ethanol solution of N-tert-butylacrylamide is 45:1, and then a surfactant, sodium dodecyl sulfate, and an initiator, ammonium persulfate, are added, the total mass of the surfactant and the initiator and the volume ratio of the mixed aqueous solution are 1 mg:1.5 mL, and the mass ratio of the surfactant and the initiator is 37.5:1. The reaction is carried out under a nitrogen atmosphere, the reaction temperature is 50°C, the reaction time is 4 hours, and the reaction mixture is dialyzed and purified in ultrapure water with a dialysis bag of MWCO1400 for 110 hours. After the dialyzate is freeze-dried, the white flocculent obtained is hydrogel nanoparticles NPs;

[0043] The concentration of N-isopropylacrylamide in the mixed aqueous solution is 3 mg / mL, the concentration of methacrylamidopropyltrimethylammonium chloride is 0.35 mg / mL, and the concentration of N,N-methylenebisacrylamide is 0.2 mg / mL; the concentration of N-tert-butylacrylamide in the anhydrous ethanol solution of N-tert-butylacrylamide is 108 mg / mL;

[0044] S2. Loading photosensitizer:

[0045] The TPA-2PY-C2 solution with a concentration of 800 μM was mixed with the hydrogel nanoparticles NPs prepared in step S1 and stirred and incubated for 10 h. After the incubation, the mixture was dialyzed and purified in ultrapure water using a dialysis bag with a MWCO of 1400 for 68 h. The dialyzate was freeze-dried to obtain an orange flocculent, which was AIE-NPs. The mass volume ratio of the hydrogel nanoparticles NPs to the TPA-2PY-C2 solution was 1 mg:5 mL.

[0046] The TPA-2PY-C2 is prepared by the following method: adding the compound 1-ethyl-4-methylpyridinium iodide and tetrahydropyrrole to an ethanol solution of 4,4,-diformyl triphenylamine at a concentration of 48 mg / mL during heating, the mass volume ratio of the compound 1-ethyl-4-methylpyridinium iodide to the ethanol solution of 4,4,-diformyl triphenylamine is 65 mg / mL, and the volume ratio of tetrahydropyrrole to the ethanol solution of 4,4,-diformyl triphenylamine is 2:1, and the obtained mixture is stirred at 75° C. for 17 hours, and the obtained product is TPA-2PY-C2;

[0047] S3. Preparation of AIE-EGF-NPs nanoparticles:

[0048] The AIE-NPs prepared in step S2 were mixed with an epidermal growth factor (EGF) solution having a protein concentration of 8 μg / mL and stirred for co-incubation for 10 h. The mass volume ratio of AIE-NPs to the epidermal growth factor (EGF) solution was 30 mg:1 mL. After the incubation, the mixture was dialyzed and purified in ultrapure water for 22 h using a dialysis bag with a MWCO of 1400. The dialysis solution was freeze-dried to obtain the flocculent AIE-EGF-NPs. Example 2: A method for preparing a hydrogel nanomaterial loaded with a photosensitizer and epidermal growth factor, comprising the following steps: S1. Preparation of hydrogel nanoparticles NPs:

[0049] A mixed aqueous solution of N-isopropylacrylamide, methacrylamidepropyltrimethylammonium chloride and N,N-methylenebisacrylamide, and an anhydrous ethanol solution of N-tert-butylacrylamide are added to a reaction bottle, the volume ratio of the mixed aqueous solution to the anhydrous ethanol solution of N-tert-butylacrylamide is 55:1, and then a surfactant, sodium dodecyl sulfate, and an initiator, ammonium persulfate, are added, the total mass of the surfactant and the initiator and the volume ratio of the mixed aqueous solution are 1 mg:2 mL, and the mass ratio of the surfactant and the initiator is 100:1. The reaction is carried out under a nitrogen atmosphere, the reaction temperature is 65°C, the reaction time is 8 hours, and the reaction mixture is dialyzed and purified in ultrapure water with a dialysis bag of MWCO1400 for 130 hours. After the dialyzate is freeze-dried, the white flocculent obtained is hydrogel nanoparticles NPs;

[0050] The concentration of N-isopropylacrylamide in the mixed aqueous solution is 4.5 mg / mL, the concentration of methacrylamidopropyltrimethylammonium chloride is 0.45 mg / mL, and the concentration of N,N-methylenebisacrylamide is 0.3 mg / mL; the concentration of N-tert-butylacrylamide in the anhydrous ethanol solution of N-tert-butylacrylamide is 124 mg / mL;

[0051] S2. Loading photosensitizer:

[0052] The TPA-2PY-C2 solution with a concentration of 1200 μM was mixed with the hydrogel nanoparticles NPs prepared in step S1 and stirred and incubated for 14 h. After the incubation, the mixture was dialyzed and purified in ultrapure water for 75 h using a dialysis bag with a MWCO of 1400. The dialyzate was freeze-dried to obtain an orange flocculent, which was AIE-NPs. The mass volume ratio of the hydrogel nanoparticles NPs to the TPA-2PY-C2 solution was 2 mg:5 mL.

[0053] The TPA-2PY-C2 is prepared by the following method: adding the compound 1-ethyl-4-methylpyridinium iodide and tetrahydropyrrole to an ethanol solution of 4,4,-diformyl triphenylamine with a concentration of 56 mg / mL during heating, the mass volume ratio of the compound 1-ethyl-4-methylpyridinium iodide to the ethanol solution of 4,4,-diformyl triphenylamine is 75 mg / mL, and the volume ratio of tetrahydropyrrole to the ethanol solution of 4,4,-diformyl triphenylamine is 3:1, and the obtained mixture is stirred at 85° C. for 15 hours, and the obtained product is TPA-2PY-C2;

[0054] S3. Preparation of AIE-EGF-NPs nanoparticles:

[0055] The AIE-NPs prepared in step S2 were mixed with an epidermal growth factor (EGF) solution having a protein concentration of 12 μg / mL and incubated for 14 hours. The mass volume ratio of AIE-NPs to vascular endothelial growth factor (EGF) solution was 40 mg:1 mL. After the incubation, the mixture was dialyzed and purified in ultrapure water for 26 hours using a dialysis bag with a MWCO of 1400. The dialysis solution was freeze-dried to obtain the flocculent AIE-EGF-NPs. Example 3: A method for preparing a hydrogel nanomaterial loaded with a photosensitizer and epidermal growth factor, which comprises the following steps: S1. Preparation of hydrogel nanoparticles NPs:

[0056] A mixed aqueous solution of N-isopropylacrylamide, methacrylamidepropyltrimethylammonium chloride and N,N-methylenebisacrylamide, and an anhydrous ethanol solution of N-tert-butylacrylamide are added to a reaction bottle, the volume ratio of the mixed aqueous solution to the anhydrous ethanol solution of N-tert-butylacrylamide is 50:1, and then a surfactant, sodium dodecyl sulfate, and an initiator, ammonium persulfate, are added, the total mass of the surfactant and the initiator and the volume ratio of the mixed aqueous solution are 1 mg:1.8 mL, and the mass ratio of the surfactant and the initiator is 78:1. The reaction is carried out under a nitrogen atmosphere, the reaction temperature is 57° C., the reaction time is 6 h, the reaction mixture is dialyzed and purified in ultrapure water with a dialysis bag of MWCO1400 for 120 h, and the dialyzate is freeze-dried to obtain a white flocculent as hydrogel nanoparticles NPs;

[0057] The concentration of N-isopropylacrylamide in the mixed aqueous solution is 4 mg / mL, the concentration of methacrylamidopropyltrimethylammonium chloride is 0.4 mg / mL, and the concentration of N,N-methylenebisacrylamide is 0.25 mg / mL; the concentration of N-tert-butylacrylamide in the anhydrous ethanol solution of N-tert-butylacrylamide is 115 mg / mL;

[0058] S2. Loading photosensitizer:

[0059] A 1000 μM TPA-2PY-C2 solution was mixed with the hydrogel nanoparticles NPs prepared in step S1 and stirred and incubated for 12 h. After the incubation, the mixture was dialyzed and purified in ultrapure water using a dialysis bag with a MWCO of 1400 for 72 h. The dialyzate was freeze-dried to obtain an orange flocculent, which was AIE-NPs. The mass-to-volume ratio of the hydrogel nanoparticles NPs to the TPA-2PY-C2 solution was 1.5 mg:5 mL.

[0060] The TPA-2PY-C2 is prepared by the following method: adding the compound 1-ethyl-4-methylpyridinium iodide and tetrahydropyrrole to an ethanol solution of 4,4,-diformyl triphenylamine with a concentration of 52 mg / mL during heating, the mass volume ratio of the compound 1-ethyl-4-methylpyridinium iodide to the ethanol solution of 4,4,-diformyl triphenylamine is 70 mg / mL, and the volume ratio of tetrahydropyrrole to the ethanol solution of 4,4,-diformyl triphenylamine is 2.5:1, and the obtained mixture is stirred at 80° C. for 16 hours, and the obtained product is TPA-2PY-C2;

[0061] S3. Preparation of AIE-EGF-NPs nanoparticles:

[0062] The AIE-NPs prepared in step S2 were mixed with an epidermal growth factor (EGF) solution having a protein concentration of 10 μg / mL and stirred for incubation for 12 h. The mass volume ratio of AIE-NPs to the epidermal growth factor (EGF) solution was 35 mg:1 mL. After the incubation, the mixture was dialyzed and purified in ultrapure water using a MWCO1400 dialysis bag for 24 h. The dialysate was freeze-dried to obtain the flocs, which were AIE-EGF-NPs.

[0063] The beneficial effects of the present invention are described below by experiments:

[0064] Example 1: A method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor, comprising the following steps: S1. Preparation of hydrogel nanoparticles NP1:

[0065] 97 mg N-isopropylacrylamide, 10 mg methacrylamidopropyltrimethylammonium chloride and 5 mg N,N-methylenebisacrylamide were dissolved in 24.5 mL distilled water, and 58 mg N-tert-butylacrylamide was dissolved in 0.5 mL anhydrous ethanol, and added to a reaction bottle, and then 250 μg surfactant sodium dodecyl sulfate SDS and 15 mg initiator APS were added, and nitrogen was passed through for 30 minutes and then heated to 60°C for 6 hours to obtain a milky white suspension. The milky white suspension obtained by the reaction was dialyzed and purified in ultrapure water with a dialysis bag of MWCO1400 for 5 days. After the dialyzate was freeze-dried, the white flocculent obtained was the hydrogel nanoparticle NP1;

[0066] S2. Loading photosensitizer:

[0067] 10 mL of 1000 μM TPA-2PY-C2 solution was mixed with the hydrogel nanoparticles NP1 prepared in step S1 and stirred for 12 h. After the incubation, the mixture was dialyzed and purified in ultrapure water using a dialysis bag with MWCO1400 for 72 h. The dialyzate was freeze-dried to obtain an orange flocculent, which was AIE-NP1.

[0068] Wherein, the TPA-2PY-C2 is prepared by the following method: adding compound 1-ethyl-4-methylpyridinium iodide (535 mg, 2.66 mmol, 2.00 eq. CAS: 54778-76-6) and tetrahydropyrrole (20 μL) to a solution of 4,4-diformyl triphenylamine (400 mg, 1.33 mmol, 1.00 eq.) in ethanol (7.5 mL) during heating, stirring the resulting mixture at 80° C. for 16 h, concentrating in vacuo, and separating and purifying the crude product by silica gel chromatography (methanol: dichloromethane = 0-20%) to obtain a red solid compound (360 mg, yield 40%);

[0069] S3. Preparation of AIE-EGF-NP1 nanoparticles:

[0070] The AIE-NP1 prepared in step S2 was mixed with 10 mL of an epidermal growth factor (EGF) solution with a protein concentration of 10 μg / mL and stirred for 12 h. After the incubation, the solution was dialyzed and purified in ultrapure water using a dialysis bag with MWCO1400 for 24 h. The dialysate was freeze-dried to obtain a flocculent AIE-EGF-NP1.

[0071] Example 2: The preparation method is the same as Example 1, except that the amount of SDS added is different: 1.25 mg of surfactant sodium dodecyl sulfate SDS is added to obtain NP2 with a particle size different from NP1, and AIE-EGF-NP2 is prepared.

[0072] Example 3: The preparation method is the same as Example 1, except that the amount of SDS added is different: 5 mg of surfactant sodium dodecyl sulfate SDS is added to obtain NP3 with a particle size different from NP1 and NP2, and AIE-EGF-NP3 is prepared.

[0073] Example 4: The preparation method is the same as Example 1, except that the amount of SDS added is different: 10 mg of surfactant sodium dodecyl sulfate SDS is added to obtain NP4 with a particle size different from NP1, NP2, and NP3, and AIE-EGF-NP4 is prepared.

[0074] 1. Hydrogel Nanoparticles NPs

[0075] Four hydrogel nanoparticles NP1, NP2, NP3 and NP4 with different particle sizes were synthesized in Examples 1 to 4. Their morphologies were observed by SEM. The prepared hydrogel nanoparticles NP1, NP2, NP3 and NP4 were spheres with relatively uniform sizes. The sizes of the four hydrogel nanoparticles NP1 to NP4 decreased successively, and the diameters were about 70nm-300nm. Figure 1 The particle size distribution of NP1, NP2, NP3 and NP4 was tested by dynamic light scattering (DLS) experiment, and the particle sizes were measured to be 310nm, 229nm, 125nm and 79nm respectively, and the polydispersity index (PDI) was less than 0.1, showing monodispersity. The experimental results showed that the prepared hydrogel nanoparticles were spherical polymers with uniform size.

[0076] 2. Characterization of Hydrogel Nanoparticles

[0077] The results are as follows Figure 2 As shown. The loading efficiency of the AIE-NPs prepared in Examples 1-4 was calculated by measuring the amount of TPA-2PY-C2 aggregates in the AIE-NPs using a UV-visible photometer, and was determined by dissolving them in chloroform and plotting a standard curve for different concentrations of TPA-2PY-C2. It was found that the drug loading rate of the nanoparticles increased with the increase of the particle size ( Figure 2 a), Since high drug loading can achieve the maximum bactericidal effect, subsequent studies all used NP1 as a nanocarrier.

[0078] The photosensitivity of the AIE-EGF-NPs prepared in Example 1 was studied by measuring the amount of reactive oxygen species (ROS) produced. Figure 2 As shown in Figure 2, we used 2',7'-dichlorodihydrofluorescein (DCFH) as a fluorescent indicator. In the presence of ROS, DCFH emits green fluorescence at around 524 nm. Figure 2As shown in b, the fluorescence signal of NPs is negligible, indicating that it does not produce ROS. In contrast, AIE-NPs showed nearly 90-fold emission enhancement after 60 seconds of illumination, demonstrating its excellent ROS generation ability. At the same time, the fluorescence emission of AIE-EGF-NPs was lower than that of AIE-NPs, which may be due to the effect of EGF on the surface of nanoparticles through electrostatic adsorption. In addition, ABDA is a type II indicator for detecting the generation of singlet oxygen, and its decomposition degree can reflect the presence of singlet oxygen. Figure 2 As shown in Figure c, after 100 seconds of light treatment, approximately 60% of ABDA in the AIE-NPs group and the AIE-EGF-NPs group was decomposed. Under the same experimental conditions, no changes were observed in the NPs group. These reactive oxygen species assay results indicate that AIE-EGF-NPs can efficiently generate reactive oxygen species under light, thus endowing the hydrogel nanoparticles with excellent photodynamic inactivation effects. We further studied the stability of AIE-EGF-NPs, as this is key to their continuous application. After 5 days of storage at room temperature, we recorded a consistent particle size distribution of AIE-EGF-NPs, verifying their stability ( Figure 2 d) Subsequently, we prepared AIE-EGF-NPs suspension and stored it at room temperature for 5 consecutive days to study its spontaneous release rate. Figure 2 As shown in Figure 5, only 4.97% ± 2.22% of TPA-2PY-C2 was detected in the solution, indicating that its spontaneous release rate was very low and the encapsulation remained intact. Next, we performed potentiometric measurements on it. The zeta potential measurement of NPs showed that its positive surface charge was 19.12 mV, while after loading the positively charged TPA-2PY-C2 and the negatively charged EGF, the surface charge of NPs slightly decreased to 15.85 mV ( Figure 2 f).

[0079] 3. Characterization of antibacterial properties

[0080] The results are as follows Figure 3 As shown. The minimum inhibitory concentration of hydrogel nanoparticles AIE-EGF-NP1 was determined by the coating plate counting method. Figure 3 It can be seen that compared with the control group, when the mass concentration of AIE-EGF-NPs was 62.5μg / mL under light conditions, the hydrogel nanoparticles had a significant inhibitory effect on common Gram-negative bacteria, with an inhibition rate of 80%. When the mass concentration of AIE-EGF-NPs reached 0.5mg / mL, it had a complete inhibitory effect on Gram-negative bacteria, with an antibacterial rate of 100%. We then co-incubated AIE-EGF-NPs with two Gram-negative bacteria suspensions to determine the bacterial growth curve, as shown in Figure 1. Figure 3As shown in b and 3c, the AIE-EGF-NPs group showed a complete inhibitory effect on bacterial growth compared with the control group, which further confirmed the efficient inactivation ability of AIE-EGF-NPs against Gram-negative bacteria.

[0081] 4. Research on antibacterial mechanism

[0082] Since the nanoparticles are unlikely to pass through the membrane and be taken up by bacterial cells, the working mechanism of AIE-EGF-NPs for bacterial labeling was further investigated. Figure 4 As shown, SEM analysis confirmed our assumption that the hydrogel nanoparticles AIE-EGF-NPs (Example 1) with positive surface charge were tightly adsorbed on the negatively charged Gram bacteria on the cell surface through electrostatic action, and the TPA-2PY-C2 carried in the hydrogel nanoparticle network system triggered by light produced highly efficient reactive oxygen species that destroyed the integrity of the bacterial cell membrane. The bacteria showed severe morphological damage, with wrinkles on the surface, flattened, with small holes, and overflow of contents. In contrast, the bacteria treated with the blank control group maintained good bacterial morphology.

[0083] 5. Biocompatibility of hydrogels

[0084] The results are as follows Figure 5 As shown, to evaluate the biocompatibility of AIE-EGF-NPs hydrogel nanoparticles (Example 1) with wounds, a live / dead staining assay was performed on mouse fibroblasts (L929) cells ( Figure 5 a). The results showed that AIE-EGF-NPs hydrogel nanoparticles had no adverse effects on cell viability. The cell morphology of the control group and the hydrogel group was intact under laser confocal microscopy, indicating satisfactory cell compatibility. The viability of mouse fibroblasts (L929) was determined using the CCK-8 cell viability assay ( Figure 5 b, 5c), the experimental results are consistent with the conclusions obtained by live / dead staining, which once again proves that AIE-EGF-NPs hydrogel nanoparticles are non-toxic and reliable in safety. In addition, considering the potential contact between AIE-EGF-NPs hydrogel nanoparticles and blood, the hemocompatibility of the hydrogel was evaluated using a hemolysis test ( Figure 5 d). The results showed that AIE-EGF-NPs hydrogel nanoparticles did not induce significant hemolysis of erythrocytes (hemolysis rate <5%). These results all indicate that AIE-EGF-NPs hydrogel nanoparticles have excellent biocompatibility.

[0085] 6. Cell Migration Assay

[0086] In addition, hydrogel nanoparticles can mimic the extracellular matrix, providing cells with an environment for support and signal transmission. This simulation can not only help study cell behavior, but also play an important role in tissue engineering and regenerative medicine. Therefore, a scratch test was applied to evaluate the ability of AIE-EGF-NPs hydrogel nanoparticles (Example 1) to promote cell migration. Figure 6 As shown in the figure, compared with the control group, AIE-EGF-NPs hydrogel nanoparticles can significantly promote the migration of L929 cells, and the migration rate is significantly faster than that of the AIE-NPs group. This may be due to the bioactive factor EGF introduced into the AIE-EGF-NPs hydrogel nanoparticles providing the signal required for cell migration. Therefore, AIE-EGF-NPs hydrogel nanoparticles have excellent wound healing ability, which is of great significance for wound repair and angiogenesis.

[0087] 7. Mouse wound infection model experiment

[0088] A mouse full-thickness wound infection model was established to comprehensively evaluate the wound healing performance of AIE-EGF-NPs hydrogel nanoparticles (Example 1). 15-day-old Balb / c mice were selected, and full-thickness skin incisions were made on the back of the mice. Staphylococcus aureus was then treated at the incision for one day to simulate bacterial infection. Different preparations were then applied. The blank control group was treated with PBS. The results are shown in Figure 2. Figure 7 As shown, Figure 7 a shows the wound photos of different treatment groups (including PBS, NPs, AIE-NPs, AIE-EGF-NPs, and AIE-NPs and AIE-EGF-NPs combined with light treatment) in the mouse wound infection model at different time points (day 0, day 3, day 6, and day 9). In order to evaluate wound regeneration, we measured and analyzed the wound size ( Figure 7 b) The results showed that the infected wound area of ​​the AIE-EGF-NPs group combined with light treatment was significantly reduced on the 9th day, and its healing rate was as high as 92%, and this group healed the fastest. In contrast, the other groups showed obvious ulcers and exudate throughout the recovery period, especially the control group, which had a healing rate of only 46% on the 9th day. In addition, the weight recovery rate of mice in the AIE-EGF-NPs+L group was also significantly faster than that of the control group ( Figure 7 c) These results indicate that AIE-EGF-NPs combined with light irradiation exhibited strong in vivo antibacterial activity and the ability to accelerate skin healing.

[0089] We performed histological analysis on the wound surface on day 14 using hematoxylin-eosin (H&E) staining and Masson staining. The results of H&E staining showed that compared with the control group, the connective tissue in the treatment group was denser, the number of new hair follicles increased, inflammation was significantly reduced, and the epidermal thickness increased ( Figure 7 ). At the same time, Masson staining results showed that during the healing process, the amount of regenerated collagen in the wound surface gradually increased (marked in blue). The AIE-EGF-NPs+L group showed the most collagen deposition and the highest density, which was significantly better than the control group. This result further supports the view that the hydrogel nanoparticles can be used as wound repair materials to effectively promote wound healing. In addition, we performed histological analysis of the main organs of mice (including liver, spleen, kidney, heart and lung) by H&E staining, such as Figure 8 The results showed that after 14 days of treatment in mice, no abnormal reactions or obvious organ damage were observed, indicating that hydrogel nanoparticles combined with photodynamic therapy are a safe and effective wound healing treatment.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor, characterized in that: It includes the following steps: S1. Preparation of hydrogel nanoparticles NPs: A mixed aqueous solution of N-isopropylacrylamide, methacrylamidopropyltrimethylammonium chloride and N,N-methylenebisacrylamide, and an anhydrous ethanol solution of N-tert-butylacrylamide are added to a reaction bottle, and then a surfactant and an initiator are added, and the reaction is carried out under a nitrogen atmosphere. The reaction temperature is 50-65° C., the reaction time is 4-8 hours, and the reaction mixture is post-treated to obtain hydrogel nanoparticles NPs; S2. Loading photosensitizer: The photosensitizer is loaded on the hydrogel nanoparticles NPs prepared in step S1, and AIE-NPs are obtained after purification and freeze-drying; The photosensitizer is TPA-2PY-C2, which is prepared by the following method: adding compounds 1-ethyl-4-methylpyridinium iodide and tetrahydropyrrole to an ethanol solution of 4,4,-diformyl triphenylamine with a concentration of 48-56 mg / mL during heating, the mass volume ratio of the compound 1-ethyl-4-methylpyridinium iodide to the ethanol solution of 4,4,-diformyl triphenylamine is 65-75 mg / mL, and the volume ratio of tetrahydropyrrole to the ethanol solution of 4,4,-diformyl triphenylamine is 2-3:1, and the obtained mixture is stirred at 75-85° C. for 15-17 h, and the obtained product is TPA-2PY-C2; S3. Preparation of AIE-EGF-NPs nanoparticles: The AIE-NPs prepared in step S2 are mixed with the epidermal growth factor (EGF) solution and incubated for 10 to 14 hours. AIE-EGF-NPs nanoparticles are obtained after purification and freeze-drying.

2. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: In the mixed aqueous solution in step S1, the concentration of N-isopropylacrylamide is 3-4.5 mg / mL, the concentration of methacrylamidopropyltrimethylammonium chloride is 0.35-0.45 mg / mL, and the concentration of N,N-methylenebisacrylamide is 0.2-0.3 mg / mL.

3. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: The concentration of N-tert-butylacrylamide in the anhydrous ethanol solution of N-tert-butylacrylamide in step S1 is 108-124 mg / mL.

4. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: In step S1, the surfactant is sodium dodecyl sulfate, and the initiator is ammonium persulfate.

5. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: The volume ratio of the mixed aqueous solution to the anhydrous ethanol solution of N-tert-butylacrylamide is 45-55:1, the volume ratio of the total mass of the surfactant and the initiator to the mixed aqueous solution is 1 mg:1.5-2 mL, and the mass ratio of the surfactant and the initiator is 37.5-100:

1.

6. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: The post-treatment in step S1 is to dialyze and purify the reaction mixture in ultrapure water for 110 to 130 hours using a dialysis bag with MWCO1400, and the dialyzate is freeze-dried to obtain a white flocculent substance, which is the hydrogel nanoparticles NPs.

7. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: A TPA-2PY-C2 solution with a concentration of 800 to 1200 μM is mixed with the hydrogel nanoparticles NPs prepared in step S1, and then stirred and incubated for 10 to 14 hours. After the incubation, the mixture is dialyzed and purified in ultrapure water using a dialysis bag with MWCO1400 for 68 to 75 hours. The dialysate is freeze-dried to obtain an orange flocculent, which is AIE-NPs. The mass volume ratio of the hydrogel nanoparticles NPs to the TPA-2PY-C2 solution is 1 to 2 mg:5 mL.

8. The method for preparing a hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor according to claim 1, characterized in that: The protein concentration of the epidermal growth factor EGF solution in step S3 is 8-12 μg / mL, the mass volume ratio of AIE-NPs to epidermal growth factor EGF solution is 30-40 mg:1 mL, and after the incubation, the incubation is dialyzed and purified in ultrapure water with a MWCO1400 dialysis bag for 22-26 hours. The dialysate is freeze-dried to obtain a flocculent AIE-EGF-NPs.

9. A hydrogel nanomaterial loaded with photosensitizer and epidermal growth factor prepared according to the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Supramolecular metal cage, water-soluble nano-particle and preparation method and application of water-soluble nano-particle

    CN118546177A

  • Regeneration of a biocatalyst on a support material within a reactor, comprises changing the environmental conditions of the support material such that the biocatalyst is first removed and fresh biocatalyst is absorbed

    DE10207557A1